Family Communication Patterns and the Mediating Effects of Support and Resilience on Students' Concerns About College. Issue 2 (14th October 2019) - Dorrance Hall, Elizabeth; Scharp, Kristina M.; Sanders, Matthew; Beaty, Loretta
Abstract : Objective: To identify first‐year undergraduate students' concerns about college and examine how family support and resilience influence the relationships between family communication patterns and adjustment to college. Background: Nearly half of undergraduate college students in the United States do not graduate within 6 years. Low graduation rates come at high costs to students and universities. A deeper understanding of the family factors that contribute to adjustment concerns may provide retention‐focused intervention opportunities. Method: Survey data collected from precollege students ( N = 2, 252) were used to test a moderated mediation model in which family communication patterns are associated with adjustment concerns through resilience and family support. Results: Conversation orientation was related to higher family support, whereas conformity was related to lower resilience and family support. Interaction results indicate that the effects of conversation orientation on some adjustment concerns depended on conformity ratings. Resilience mediated the relationship between the orientations and adjustment concerns. Conclusion: Conversation and conformity orientation play a role in perceptions of family support, student resilience, and an array of concerns held by students as they enter college. Implications: Parents may play an important role in helping their child adjust to college through the family communication environments they create and reinforce from childhood and through the support they provide during the transition to college.